Proliferative Inhibition and Apoptotic Mechanism on Human Non-small-cell Lung Cancer (A549 Cells) of a Novel Cucurbitacin from Wilbrandia ebracteata Cogn - Silva, I. T. (2013)
Cancer represents a major public health problem from all over the world and the lung carcinoma is the leading cause of cancer death. In this sense, the aim of the present study was to examine the cytotoxic effects of a novel Cucurbitacin (Cuc1) isolated from Wilbrandia ebracteata on human non-small-cell lung cancer (A549). In order to achieve this aim, the cell proliferation was measured by MTT assay and actin cytoskeleton was stained by rhodamine-phalloidin, whereas, the cell cycle distribution and apoptosis induction were quantified using flow cytometry. The signal transduction profiling of Cuc1 treated cells, as well as the levels of apoptotic proteins were analyzed by Western blotting. Cuc1 significantly inhibited cell growth showing IC50 values of 13.5±1.8 and 3.8±0.4 μM for 48 and 72 h of treatment, respectively. Additionally, Cuc1 arrested cell cycle at G2/M phase, disrupted the actin dynamics and induced apoptosis since the amount of apoptotic cells increased from 5.18±0.585% in the untreated cells to 73.82±0.545% in the treated cells. Detailed analysis on the mechanism of action revealed that Cuc1 inhibited the phosphorylation of Protein Kinase B (PKB/AKT) and Signal Transducer and Activator of Transcription (STAT3) signaling pathways, down-regulating the expression of Bcl-2 and consequently inducing cytochrome c release from the mitochondria to the cytosol. These results suggest that the Cuc1 could be a potential candidate for cancer chemotherapy agent.